Aromaticity of the completely annelated tetraphenylenes: NICS and GIMIC characterization - Baryshnikov G. V. Gleb Vladimirovich; Karaush N. N. Nataljya Nikolaevna; Minaev B. F. Boris Filippovich; Valiev R. R. Rashid Rinatovich (2015, 2015)
Title screen